Medical rationing choices of laypeople and clinicians are often illogical and inconsistent with their own stated preferences. - Pedram Heydari; Michelle N Meyer; Christopher F Chabris (PLoS ONE)
The sudden onset, rapid spread, and later surges of the Covid-19 pandemic resulted in shortages of ventilators, pharmaceuticals, and other critical resources, leaving individual clinicians to make rationing decisions for which they had little expertise or training. In two pre-registered experiments with large samples of laypeople (N = 2007) and clinicians (N = 1256), conducted during the first year of the pandemic, we found evidence of two inconsistencies in hypothetical rationing decisions: (1) The choice of which of two patients should receive a medical treatment can be systematically affected by adding a third patient who logically should not receive the treatment (an instance of the attraction effect); (2) Decisions as to which patient should receive the treatment are inconsistent with general rationing policies that participants themselves endorse. We argue that our results provide empirical support for the necessity of predetermined policies administered by independent decision-makers to ensure fairness and consistency, as required by law and ethics, in healthcare rationing choices.